New approaches to detect and inhibit quorum sensing activity in Pseudomonas aeruginosa - Lafayette, I. H. G. (2016)
Pseudomonas aeruginosa (PA), a Gram-negative opportunistic rod with ubiquitous presence in a panoply of different environments, secretes a wide array of virulence determinants that have established it as one of the leading nosocomial pathogens. Many of these virulence factors are regulated by the quorum sensing (QS) system that responds to environmental cell density variations. PA can ultimately trigger the onset of severe acute and chronic infections, especially in immunosuppressed subjects. The QS network in PA is comprised of at least four multi-layered interconnected subsystems with hierarchical organisation. From these, three (las, rhl and pqs) play a pivotal role in the production of virulence factors (e.g., lectins and pyocyanin) with relevant participation in the development and maintenance of biofilm matrices. The QS network is divided in two major signaling pathways, the one driven by N-acylhomoserine lactone signals and the one driven by 2-alkyl-4-quinolone molecules. Two alkyl quinolones of core importance exist in PA, the 2-heptyl-3-hydroxy-4(1H)quinolone, typically recognised as the “Pseudomonas quinolone signal” (PQS) and its precursor 2-heptyl-4(1H)-quinolone (HHQ). In addition to the regulatory involvement of the las and rhl quorum sensing systems, the biosynthesis of PQS production is also positively regulated by PqsR-dependent transcription of the pqsABCDE operon (a multivirulence factor regulator also known as MvfR). For that reason, the alkyl quinolone (AQ) signalling pathway, and more specifically its major regulator PqsR, are widely seen as promising targets for novel antimicrobial approaches. Because of the growing presence of multidrug resistant PA in the clinical setting, representing both an immediate menace to immunocompromised patients and a heavy burden on hospital budgets, the development of more rapid and affordable screening strategies for detection of the pathogen are required. Thus, new screening strategies adapted to clinical samples and successful novel synthetic small PqsR antagonists can lead the way to a new Era in the battle against hyper-virulent/-resistant PA strains. Primarily focusing on the AQ system, this research project investigated three inter-related areas, namely: (a) the highthroughput screening of novel synthetic small molecule antagonists of the PqsR protein, designed for suppression of virulence-associated phenotypes, (b) the development of a luminescent PQS-based screening bioreporter to be applied in the clinical setting, and finally (c) the optimisation of a methodology combining liquid extraction surface analysis (LESA) and mass spectrometry (MS) for screening PQS-related AQs from in vivo bacterial extracts, and also intended for future screening of a variety of clinical samples (e.g., blood plasma, urine and saliva). A large number of synthetic small molecules with putative PqsR antagonism were obtained from our French partner GreenPharma, and studied for their capacity to interfere with expression of the key player of the pqs system, PqsR. By applying a rational selection strategy, based on the inhibitory effects on pqsA expression, assessment of metabolical exertion, and assay studies on the ultimate repression of key virulence-associated phenotypes (lectins LecA and LecB, pyocyanin, PQS-associated AQs) and impact on biolfilm formation, a final selection comprised of the four best antagonists was obtained. Compounds GPZ002966, GPZ004927, GPZ824390 and GPZ273902 had their cytotoxicity subsequently studied keeping in mind their applicability in pre-clinical studies. Overall, these PqsR antagonists promoted very strong inhibition of pqsA and lecA expression, strongly reduced production of pyocyanin and PQS-related AQs (HHQ, HQNO and C7-PQS itself), showed a strong degree of biofilm inhibition, with IC50 scores sitting at the nanomolar level, and no signs of metabolical arrest was reported by the test strains used. Some explanations, focusing on the functional and structural organisation/composition of these compounds are also offered based on a comparative analysis against a number of the most prolific PqsR antagonists recently developed. The bioluminescent PQS-based biosensor for the detection of PA was engineered to respond to the presence of exogenous PQS that forms a complex with the regulatory PqsR protein, ultimately stimulating the expression of a luxCDABE-fused pqsA promoter. The biosensor was subsequently inserted in a non-pathogenic E. coli recipient by means of chromosomal integration, devoid of the sdiA LuxR homolog that could potentially interfere with the recognition of PqsR. A silent reporter was observed when in E. coli, but further assessments to its genetic integrity did not reveal any single nucleotide polymorphisms (SNP). In addition, after further testings to its activity in different established PA mutants, devoid of genes that constituted the bioreporting system or to it directly associated, a fully functional bioreporter was confirmed. Finally, a few possible explanations as to what might be in the origin of a defective bioreporter in E. coli are discussed. Lastly, a new LESA-MS protocol based on the surface sampling of dried bacterial extracts, envisaging its potentialities as a rapid and cheap screening method for detection of AQs, was designed and optimised. Even though the method has been widely used in a variety of research scenarios, this is the first time LESA-MS is applied as a screening methodology in the context of bacterial extract screening. Overall, the optimisation process showed that LESA-MS is an approach with numerous potentialities and immediate advantages, where one emphasises sampling simplicity, fast delivering of results, sensitivity to AQs at the nanomolar level (especially for C7-PQS and the precursor HHQ). But simultaneously, this methodology also revealed limitations inherent to its setting up that constrain an effective screening. The most emphatic ones being the volatility of the preparations to intra-sampling variability, and to a certain degree, an unexpected insensitivity to important QS N-acyl homoserine lactones (AHLs), namely C4-HSL and 3-oxo-C12-HSL. Nevertheless, such limitations do not present themselves as an insurmountable barrier, and based on results from available studies making use of the LESA-MS a number of possibilities to work around these are also presented.